Daya Hambat Ekstrak Teripang Pasir (Holonthuria scabra) Terhadap Pertumbuhan Bakteri Mixed periodontopatogen In Vitro - Susi Krestiana; Widyastuti; Vivin Ariestania (Denta Journal Kedokteran Gigi, 2015)
Background: Periodontitis is caused by the occupation of gram-negative bacteria (mixed periodontopatogen) in oral cavity. Despite causing resistance, antibiotics are still used as a therapy for periodontitis. Sand sea cucumber (Holonturia scabra) extract hold somepotentials, if developed, to become the alternative therapy for periodontitis due to its antibacterial effects against gramnegative bacteria. Purpose: To determine sand sea cucumber extract (Holonturia scabra) in inhibiting the growth of mixed periodontopatogen bacteria. Materials and Methods: This study used a research design the post-test only control group design. 40 samples of BHI agar plates, contained mixed periodontopatogen bacteria samples, were divided into 5 groups samples. K1 (negative control) was given distilled water containing filter paper, K2 (positive control) was given the antibiotic tetracycline disc 30 g, while P1, P2, and P3 were given a filter paper containing sand sea cucumber extract with a concentration of 150 g/ml, 300 g/ml, and 450 g/ml. All sample from each group were anaerobically inoculated for 2x24 hours. After inoculation, the area aroundthe filter paper will appear to be clear and it will be measured with digital calipers (mm). The acquired data will be analyzed using the Kruskal-Wallis and Mann-Whitney test. Result: The inhibition rate of K1 (6,00 ± 0,00), K2 (28,975 ± 1,20049), P1 (6,8525 ± 0,30156), P2 (7,6237 ± 0,51281), and P3 (8,75 ± 0,3525). Conclusion: Sand sea cucumber extract (Holonthuria scabra) can inhibit the growth of Mixed periodontopatogen bacteria.